Problem-oriented and project-based learning (POPBL) as an innovative learning strategy for sustainable development in engineering education - Lehmann, M.; Christensen, P.; Du, X.; Thrane, M (European Journal of Engineering Education, 2008)
Abstract In a world where systems are increasingly larger, where their boundaries are often difficult to identify, and where societal rather than technical issues play increasingly bigger roles, problems cannot be solved by applying a technical solution alone. It thus becomes important for engineers to be skilled not only in terms of their particular technical field but also their ability to identify non-technical aspects of problems, the interaction between these aspects and possible solutions. Introducing and integrating these aspects into engineering education is certainly not an easy task and requires innovative approaches. In this article, focus is placed on the so-called Aalborg Model, a problem-oriented and project-based learning paradigm utilised at Aalborg University (Denmark), and the mutual benefits that this particular learning strategy provides for students, faculty and communities. The article discusses the concept of sustainable development; accounts for the general capabilities of engineering education graduates, and discusses the integration of non-technical issues into various environmental engineering curricula. On the basis of this discussion, it underlines the importance of applying a problem-oriented rather than a subject-oriented approach in order to create a balance between problem occurrence (or identification) and innovative problem solving. We conclude that, in order for engineers to be able to handle sustainability-related problems, their education needs to allow for interplay, mix and diversity; aspects that a problem-oriented and project-based learning approach will involve.
Keywords: apprentissage par projet